'To remain unaltered in the courage you have inherited from your ancestors' : Magdeburg under siege, 1547-1631 - Finucane, Jane (Trinity College (Dublin, Ireland). Department of History, 2008)
The siege of Magdeburg 1550-1551 became an important reference point for the city in the early years of the Thirty Years War, as demonstrated in several printed works of the 1620s. The crisis which ended in Magdeburg's destruction in 1631 has not been much studied from the point of view of print culture, although this is, due to archival depletion, a relatively useful perspective. Printed works issuing from the town are in fact numerous, although they came from a relatively small group of authors and their number declined steeply as the Thirty Years War progressed. The narrative which historians have constructed of events leading up to the siege has not changed since the late nineteenth century, despite advances in knowledge delivered from the archives. For this reason, this thesis, while examining print culture in Magdeburg in the early Thirty Years War with particular reference to the frequent recourse had by authors to the town's role in the Schmalkaldic wars of the mid-sixteenth century, offers simultaneously some elements of reconstruction to the narrative of the events of these years. The first three chapters of the thesis work almost exclusively on print culture. The fourth chapter considers the period of from Wallenstein's blockade of Magdeburg to the return of the Administrator of the Archdiocese, Christian Wilhelm of Brandenburg. The fifth chapter extends this analysis into the period of the town's Swedish alliance and the aftermath of the crisis.
Embargo End Date: 2020-05-22
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin, 2008